2023
DOI: 10.3389/fimmu.2023.1119383
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-resident memory T cells in gastrointestinal tumors: turning immune desert into immune oasis

Abstract: Tissue-resident memory T cells (Trm) are a particular type of T cell subgroup, which stably reside in tissues and have been revealed to be the most abundant memory T cell population in various tissues. They can be activated in the local microenvironment by infection or tumor cells and rapidly clean them up to restore homeostasis of local immunity in gastrointestinal tissues. Emerging evidence has shown that tissue-resident memory T cells have great potential to be mucosal guardians against gastrointestinal tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 139 publications
0
1
0
Order By: Relevance
“…Similarly, when co-cultured with breast cancer cells, it was found that CD8 + CD69 + CD103 + TRM exhibited higher levels of IFNG and tumor necrosis factor-alpha (TNF-α) compared to CD8 + CD69 + CD103 − T cells, further mediating a more significant tumor-killing effect [32]. The augmentation of tumor-resident memory T cells correlated with improved survival outcomes in melanoma patients undergoing immunotherapy [33,34]. In addition, TRM could convert "cold" into "hot" tumors, thereby improving the effectiveness of immunotherapy in gastrointestinal tumors [35].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when co-cultured with breast cancer cells, it was found that CD8 + CD69 + CD103 + TRM exhibited higher levels of IFNG and tumor necrosis factor-alpha (TNF-α) compared to CD8 + CD69 + CD103 − T cells, further mediating a more significant tumor-killing effect [32]. The augmentation of tumor-resident memory T cells correlated with improved survival outcomes in melanoma patients undergoing immunotherapy [33,34]. In addition, TRM could convert "cold" into "hot" tumors, thereby improving the effectiveness of immunotherapy in gastrointestinal tumors [35].…”
Section: Discussionmentioning
confidence: 99%
“…The rising incidence and often late-stage diagnosis of these malignancies underscore the urgency of developing effective treatment strategies. Recently, cancer immunotherapy has shown remarkable progress in the treatment of various cancers; however, the role of tissue-resident memory T cells (Trm cells) in gastrointestinal cancers has become a subject of increased interest [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%